Effect of strength on carbonation depth / A.B.M. Diah … [et al.] - Diah, A.B.M.; Majid, T.A; Jelani, A.; Kamarulzaman, K.B; Ridzuan, A.R.M. (2002)
Carbonation is main durability problem. Factors influencing carbonation such as curing regime, water/cement ratio, age of the concrete, type of aggregate, cement replacement material and strength are widely published. This paper will discusses on the effect of concrete strength on carbonation of concrete. OPC concrete cubes 100 mm3 of design strength at 20, 30, 40, 50, 60. 70, and 80 N/mm2 have been investigated. This covers a wide range of concrete strength used in industry. All concrete samples cured in water 28 days prior exposed into accelerated carbonation camber with 4% carbon dioxide concentration. Carbonation depth was measured for 5, 10, 15, 20, 25 and 30 weeks exposed. The results shown carbonation depth on strength and decreased as strength of concrete was increased.